(untitled) (Research in Agriculture Livestock and Fisheries, 2021)
Duck plague is an enveloped DNA virus that belongs to the Anatid Herpes Virus; the Herpesviridae family is an acute and highly infectious duck, geese, and swan disease that causes tremendous economic losses of duck rearing in Bangladesh and other duck rearing countries. Therefore, we decided to isolate duck plague virus from recent fields’ outbreaks area and performed molecular detection and phylogenetic analysis to find out the similarities between our findings and other isolates around the world. Visceral organs of 13 suspected ducks from recent outbreaks area were collected by post-mortem examination for inoculum preparation. Several passages were performed to harvest into 9-11 old embryonated eggs Chorioallantoic membrane (CAM) route and duck embryo fibroblast (DEF) primary cell culture. DNA polymerase (446bp) and DNA polymerase (UL, 602bp) genes were used for molecular detection by Polymerase chain reaction (PCR). Pathogenicity was done with duckling and TCID50 on DEF. Molecular characterization was performed from extracted DNA of duckling and 2 Positive PCR products were partially sequenced for phylogenetic analysis of their origin and nucleotide variations. Sequenced data was analyzed to reveal genetic relationships among constructed phylogenetic tree for understanding potential transmission with origin of virus and data was then submitted to gene bank and got accession number for DPV-BR1-MN937272 and DPV-BR-2-MN937273. Among 13 samples, 4(30.77%) were found positive by PCR using DNA polymerase at 446 bp and UL at 602 bp gene. Chorioallantoic membrane (CAM) was observed hemorrhagic after 72 days and duck embryo fibroblast (DEF) become round as showed cytopathic characteristics after 48h of infection .Duckling showed that isolated virus was highly pathogenic as characteristics signs of post-mortem examination. Therefore, this has found that recent isolates have similarity with Bangladesh, India and China isolates. Moreover, TCID50 has confirmed the isolates have accepted titer to be a vaccine strain. Res. Agric., Livest. Fish.8(1): 125-133, April 2021